Current gaps in management and timely referral of cardiorenal complications among people with type 2 diabetes mellitus in the Middle East and African countries: Expert recommendations. Issue 5 (17th April 2022) - Sonmez, Alper; Sabbour, Hani; Echtay, Akram; Rahmah, Abbas Mahdi; Alhozali, Amani Matook; al Sabaan, Fahad Sulman; Haddad, Fares H.; Iraqi, Hinde; Elebrashy, Ibrahim; Assaad, Samir N.; Bayat, Zaheer; Osar Siva, Zeynep; et al.
Abstract: The upsurge of type 2 diabetes mellitus is a major public health concern in the Middle East and North Africa (MENA) and Africa (AFR) region, with cardiorenal complications (CRCs) being the predominant cause of premature morbidity and mortality. High prevalence of cardiometabolic risk factors, lack of awareness among patients and physicians, deficient infrastructure, and economic constraints lead to a cascade of CRCs at a significantly earlier age in MENA and AFR. In this review, we present consensus recommendations by experts in MENA and AFR, highlighting region‐specific challenges and potential solutions for management of CRCs. Health professionals who understand sociocultural barriers can significantly increase patient awareness and encourage health‐seeking behavior through simple educational tools. Increasing physician knowledge on early identification of CRCs and personalized treatment based on risk stratification, alongside optimum glycemic control, can mitigate therapeutic inertia. Early diagnosis of high‐risk people with regular and systematic monitoring of cardiorenal parameters, development of region‐specific care pathways for timely referral to specialists, followed by guideline‐recommended care with novel antidiabetics are imperative. Adherence to guideline‐recommended care can catalyze utilization of sodium glucose cotransporter 2 inhibitors and glucagon‐like peptide 1 receptor agonists with demonstrated cardiorenal benefits—thus paving the way for overcoming care gaps in a cost‐effective manner. Leveraging digital technology like electronic medical records can help generate real‐world data and provide insights on voids in adoption of newer antidiabetic medications. A patient‐centric approach, collaborative care among physicians from different specialties, alongside involvement of policy makers are key for improving patient outcomes and quality of care in MENA and AFR. Abstract : Highlights This consensus document identifies challenging areas and strategic recommendations for the effective management of cardiorenal complications in type 2 diabetes mellitus in the Middle East and North Africa and Africa. There is a need for optimum glycemic control, early identification of cardiorenal complications, along with risk management through optimal low‐density lipoprotein cholesterol and blood pressure control, smoking cessation, and lifestyle management. Suboptimal use of international guidelines and treatment inertia delay initiation of adequate therapy. Early diagnosis of high‐risk people with regular and systematic monitoring of cardiorenal parameters, development of region‐specific care pathways for timely referral to specialists, followed by guideline‐recommended care with novel antidiabetics are imperative for optimal management. 摘要: 2型糖尿病是中东及北非(MENA)和非洲(AFR)地区的一大公共卫生问题，心肾并发症(CRC)是过早发病和死亡的主要原因。心脏代谢危险因素的高发、患者和医生缺乏认识、基础设施不足以及经济限制导致MENA和AFR患者的CRC年龄显著提前。在这篇综述中，我们提出了MENA和AFR地区专家的共识和建议，强调了区域特有的挑战和潜在的区域控制中心管理解决方案。了解社会文化障碍的卫生专业人员可以通过简单的教育工具显著提高患者的意识并鼓励寻求健康的行为。增加医生在早期识别CRC和基于风险分层的个性化治疗方面的知识，同时更好地控制血糖，从而减轻治疗的惰性。必须对高危人群进行早期诊断，对心肾功能进行定期和系统的监测，制定特定区域的护理路径，及时转诊至专家，然后根据指南建议的治疗，使用新型抗糖尿病药物。遵循指南推荐的治疗可以使用钠葡萄糖共转运体2抑制剂和胰高血糖素样肽1受体激动剂，它们已被证明对心肾有好处，从而以经济高效的方式为治疗技术的鸿沟铺平道路。利用数字技术，如电子病历，可以辅助生成真实世界的数据，以填补对较新的抗糖尿病药物效果观察的空白。以患者为中心的方法、不同专科医生之间的协作护理以及政策制定者的参与是改善MENA和AFR地区患者结局和治疗质量的关键。